2015
DOI: 10.1111/apa.13034
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting, latchment and displacement: a mini review of early instinctual behaviour in newborn infants influencing breastfeeding success

Abstract: Instinctive behaviours have evolved favouring the mother–infant dyad based on fundamental processes of neurological development, including oral tactile imprinting and latchment. Latchment is the first stage of emotional development based on the successful achievement of biological imprinting. The mechanisms underpinning imprinting are identified and the evolutionary benefits discussed.ConclusionIt is proposed that the oral tactile imprint to the breast is a keystone for optimal latchment and breastfeeding, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…In the US, Pennsylvanians have significant doubts about the credibility of scientists on this issue . Some residents believe that experts have intentionally avoided researching cases of cancer close to wells, fearing the implications of potential findings, and others raised concerns about possible bias in scientific studies funded by industry; a concern also voiced in the UK recently . ‘Trust’ in experts does not of course necessarily translate to attitude change, and whilst Lachapelle and Montpetit note that Quebecers adjust their perceptions of risk when provided with new scientific information, they found that even a strong signal from credible experts was unlikely to alter negative attitudes to such an extent as to produce overall support.…”
Section: Perceptions Of Shale Operations In the Us And Canadamentioning
confidence: 99%
“…In the US, Pennsylvanians have significant doubts about the credibility of scientists on this issue . Some residents believe that experts have intentionally avoided researching cases of cancer close to wells, fearing the implications of potential findings, and others raised concerns about possible bias in scientific studies funded by industry; a concern also voiced in the UK recently . ‘Trust’ in experts does not of course necessarily translate to attitude change, and whilst Lachapelle and Montpetit note that Quebecers adjust their perceptions of risk when provided with new scientific information, they found that even a strong signal from credible experts was unlikely to alter negative attitudes to such an extent as to produce overall support.…”
Section: Perceptions Of Shale Operations In the Us And Canadamentioning
confidence: 99%
“…In low and middle income countries where supply of clean water is limited and hygiene of the mother and child is poor, substituting breastmilk with other fluids or food is likely to introduce pathogens resulting in infection-related infant mortality and morbidity [5]. Furthermore, the introduction of other fluids and foods reduces the frequency of breastfeeding and contributes to reduced milk production, ultimately affecting milk supply [6]. A recent systematic review showed that there were higher rates of infant deaths among 0-5 months infants who were not breastfed, partially breastfed or predominantly breastfed compared to those who were exclusively breastfed [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a review published in this issue, Elsie Mobbs et al describe the need for immediate and sustained contact, including co-sleeping, to establish optimal breastfeeding, neonatal attachment and brain growth (6). To support this model and take it even further, James McKenna and Lee Gettler propose a new word and concept -breastsleeping -a combination of breastfeeding and bedsharing in the absence of all known hazardous factors (7).…”
Section: Breastsleeping As a New Word And Conceptmentioning
confidence: 99%